Mental Health and Physical Activity in Health-Related University Students during the COVID-19 Pandemic - Talapko, Jasminka (Healthcare (Basel), 2021)
The coronavirus disease 2019 (COVID-19) pandemic led to increased negative emotional states among students. Physical activity is known to have positive impacts on mental health and well-being. However, due to the closure of gyms and other recreational facilities as a restrictive measure, students’ physical activity levels may decrease. This cross-sectional study aimed to determine the prevalence of depression, anxiety, and stress symptoms and physical activity among health-related students during the second partial COVID-19 lockdown. The study included 823 students from the Faculty of Dental Medicine and Health of the University of Osijek in Croatia. The Depression Anxiety Stress Scale-21 (DASS-21) and the Godin-Shephard Leisure Time Questionnaire for Physical Activity (GSLTPAQ) questionnaires were used to assess the prevalence of depression, anxiety, and stress symptoms as well as physical activity. Two-thirds (59.2%) of students in health-related fields were insufficiently active, while the prevalence of depression (50.8%), anxiety (50.9%), and stress (49.9%) symptoms were high. Also, female respondents had significantly higher levels of depression, anxiety, and stress than their male counterparts. Graduate students had higher levels of all three negative emotional states, but only anxiety levels were significant. This study shows that students in health-related fields had reduced physical activity and a high prevalence of negative emotional conditions (depression, anxiety, and stress) during the second partial lockdown. The resulting symptoms were mostly of mild intensity; however, we consider this a significant mental health issue during the COVID-19 pandemic. Hence, it is crucial to control and support students’ mental health, especially in more affected female individuals, in order to reduce the pandemic’s negative impact.